Inheritance of characteristics of ear productivity in hybrids between spring spelt (T. spelta L.) and soft spring wheat - Нінієва, А. К. (Scientific Progress & Innovations, 2012)
Levels of display and inheritance of productivity traits in early generations of the hybrids between spring spelt and spring soft wheat in comparison with parental forms, relationships between the traits, impact of weather conditions on these were revealed. In the F1 hybrids, the hybrid depression most often occurred. In the F2 hybrids, the plants that exceed the best parental form for all the traits of ear were detected in all combinations in the year with more favorable conditions for growth.